Sialoendoscopy, sialography, and ultrasound: a comparison of diagnostic methods - Pniak, Tomáš; Štrympl, Pavel; Staníková, Lucia; Zeleník, Karol; Matoušek, Petr; Komínek, Pavel (Open medicine, 2016)
OBJECTIVE: To compare the accuracy of ultrasound, sialography, and sialendoscopy for examining benign salivary gland obstructions.METHODS:In this prospective study, patients with symptoms of obstruction of the major salivary gland duct system presenting at the ENT Clinic University Hospital, Ostrava, from June 2010 to December 2013 were included. All patients (n=76) underwent ultrasound, sialography, and sialoendoscopy. The signs of sialolithiasis, ductal stenosis, or normal findings were recorded after the examinations. Statistical analysis of the sensitivity and specificity of all the methods was performed, as well as a comparison of the accuracy of each method for different kinds of pathology (sialolithiasis or stenosis).RESULTS: The sensitivity of ultrasound, sialography, and sialoendoscopy for sialolithiasis findings were 71.9%, 86.7 %, and 100%, respectively. The sensitivity of sialography and sialoendoscopy for stenosis of the duct was 69.0%, and 100%, respectively. The study showed impossibility of ultrasonic diagnostics of ductal stenosis. The sensitivity of sialoendoscopy for both pathologies was significantly higher than that from ultrasound or sialography (p<0.05). The specificity of sialoendoscopy was significantly higher than that from by ultrasound or sialography (p<0.05).CONCLUSION:Sialoendoscopy was the most accurate method for examination ductal pathology, with significantly higher sensitivity and specificity than by ultrasound or sialography.
Keywords: Salivary Gland Calculi; lidé; Sialography; Constriction, Pathologic; sialografie; stenóza; kaménky ve slinných žlázách; Salivary Gland Diseases; nemoci slinných žláz; Humans